LOS GENEROS DE AMIBAS PARASITAS - BELTRAN, ENRIQUE (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
A survey of the history of discovery of parasitic amebae, and comments on a few taxono-mic entanglements, is followed by a list of genera in which are cited the name of each genus, author or authors, date of proposal, meaning of the name, type sp with th
REV SOC MEX HIST NAT
Keywords: GENEROS, AMIBAS PARASITAS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); PROTOZOOLOGIA